Long-term outcome in a case of shaken baby syndrome. (April 2016) - Bartschat, Svenja; Richter, Carolin; Stiller, Dankwart; Banschak, Sibylle
Shaken baby syndrome is one of the most common causes of disability and death in infants younger than one year of age. The syndrome is the result of major mechanical forces affecting the head and central nervous system. The outcome for surviving children is often poor, with both physical and mental disabilities. Multicystic encephalomalacia has been reported as a finding after such shaking. The present case involves a one-month-old boy who was brought to hospital by his father because of somnolence and feeding aversion. Radiological imaging revealed subdural haematomas, and fundoscopy found retinal haemorrhages. During police interrogation, the father confessed to having shaken the infant. Cranial ultrasonography subsequently showed increasing damage of the brain; the boy's general condition worsened. Eight weeks after admission, he died due to renal insufficiency. Upon autopsy, the brain was atrophic, with massive pseudocystic changes of the parenchyma. The case presented impressively shows the possible serious outcome of an admitted incident of shaking and emphasises the importance of an accurate education of parents about its severe and possible lethal consequences.